Carpal Tunnel Syndrome. Issue 4 (1st August 2005) - Hui, Andrew C. F.; Wong, Shiu-man; Griffith, James
Abstract : EPIDEMIOLOGY Carpal tunnel syndrome is the most common entrapment neuropathy encountered in electro-diagnostic laboratories. It is due to compression of the median nerve in the carpal tunnel. From the number of electrophysiologically confirmed cases in Canterbury, UK, the annual incidence is 120 per 100 000 for women and 60 per 100 000 for men (Bland & Rudolfer 2003). The incidence rises with age in men, but peaks in the 45–54 age group in women. Population surveys reveal a prevalence of 0.6–2% in men and up to 9% in women (De Krom et al . 1992; Atroshi et al . 1999). However, this sex ratio varies widely in the literature, from an excess of women of 23 : 1 in Korea to 2 : 1 in the UK. The relationship between carpal tunnel syndrome and work conditions is controversial. Early epidemiological studies produced divergent results, perhaps because they were methodologically flawed –